A culture of conspiracy: apocalyptic visions in contemporary America - Barkun, Michael (Comparative studies in religion and society, 2013)
Machine generated contents note 1 The Nature of Conspiracy Belief -- 2 Millennialism, Conspiracy, and Stigmatized Knowledge -- 3 New World Order Conspiracies I: The New World Order and the Illuminati -- 4 New World Order Conspiracies II: A World of Black Helicopters -- 5 UFO Conspiracy Theories, 1975-1990 -- 6 UFOs Meet the New World Order: Jim Keith and David Icke -- 7 Armageddon Below -- 8 UFOs and the Search for Scapegoats I: Anti-Catholicism and Anti-Masonry -- 9 UFOs and the Search for Scapegoats II: Anti-Semitism among the Aliens -- 10 September 11 Conspiracies: The First Phase -- 11 September 11 Conspiracies: The Second Phase -- 12 Conspiracy Theories about Barack Obama -- 13 Conspiracists and Violence -- 14 Apocalyptic Expectations about the Year 2012 -- 15 Conclusion